Analyzing the Effect of Work-Life Balance and Work Stress on Employee Engagement in MSMEs: A Mediation Approach - Mardaus Purba; Mery Sulianty H Sitanggang; Lennaria L Tarigan (Jurnal Ilmiah Manajemen Kesatuan, 2026)
In the context of increasingly competitive business environments, maintaining employee well-being has become a critical concern for organizational success. This study examines the structural relationships among work-life balance, work stress, and employee engagement in MSMEs. Employing a quantitative approach, we analyzed data from 250 respondents using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with bootstrapping for robust parameter estimation. The findings reveal that work-life balance exerts a positive yet relatively weak influence on work stress. The direct effect of work-life balance on employee engagement is negative and statistically limited, indicating that balance alone does not automatically foster stronger involvement at work. In contrast, work stress demonstrates a positive association with employee engagement, suggesting that certain levels of stress may function as constructive challenges that stimulate dedication and focus. Mediation analysis confirms that work stress serves as an intervening mechanism linking work-life balance to employee engagement. Although the model explains a modest proportion of variance, its predictive relevance remains statistically meaningful. These results highlight the nuanced psychological dynamics shaping engagement in resource-constrained organizational environments.